Historisitas Hadis Menurut M. Mustafa Azami - Ahmad Isnaeni (Qur'an and Hadith Academic Society, 2014)
The historicity of hadith is still debated in modern hadith studies. The discussion of the historicity of hadith will demonstrate how far the authenticity of hadith can be upheld academically. Azami has responded to the views which question the historicity of hadith. He criticizes not only the Orientalists but also Muslims such as al-Asqalani and al-Baghdadi. Therefore, this paper will analyze the historicity of hadith according to Azami.